Primary cutaneous aspergillosis presenting as a cystic lesion in the foot - Shrestha, Sarik Kumar; Poudel, Rishi Ram; Bajracharya, Yogesh; Pradhan, Nabees Man Singh; Thapa, Rojin (Journal of Patan Academy of Health Sciences, 2023)
Aspergillosis is a fungal infection, usually affecting the lungs, mostly in immunocompromised patients. Musculoskeletal or cutaneous involvement is extremely rare and when it does occur, the diagnosis and treatment is delayed. We present a case of primary cutaneous aspergillosis presenting as a cyst in the foot of a 54-year-old immunocompetent female. She presented with the complaint of painful lump over right foot at the region of the fourth webspace. Magnetic Resonance Imaging (MRI) was suggestive of infected ganglion cyst. However, histopathological examination showed granulomas with areas of caseous necrosis and silver stain showed multiple fungal hyphae with morphology suggestive of Aspergillus species.